Public sector accounting - Jones, Rowan; Pendlebury, M. W. (London ; Marshfield, Mass. : England, : Pitman, Pearson, 1992)
Bringing together literature from diverse sources to cover budgeting, financial accounting and reporting, auditing and comparative international studies, this collection covers 40 years of public sector accounting.
Includes bibliographical references and index.
oif 11/03/15
Loan
Keywords: Finance, Public; Government accounting; Program and performance budgeting; Zero-base budgeting